Pengaruh Sistem Pengendalian Intern Penggajian dan Sistem Informasi Akuntansi Penggajian terhadap Penggajian - Dwi Septiani (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2016)
Employee payroll system has been centralized means the payroll procedure is not set in the offices of their own area, but a distribution office that govern them. This research was conducted at PT. PLN (Persero) Distribution of Jakarta and Tangerang Area Bulungan. The data used is the employee payroll data from January 2012-December 2013. This study aims to determine the application and implementation of the internal control system of payroll and payroll accounting information system to the payroll at PT. PLN (Persero) Distribution of Jakarta and Tangerang Bulungan area, whether it has been carried out properly or not in practice. The method used is the method of observation and interview methods. The results showed partial correlation value between the internal control system of payroll and payroll accounting information system of the payroll amounted to 0,929 with the level of the relationship is very strong and partial correlation coefficients that t count 11.505> t table 2,080 which means there is a significant relationship between the internal control system of payroll and information systems payroll accounting to payroll at PT. PLN (Persero) Distribution of Jakarta and Tangerang Area Bulungan. And the results of multiple regression test of 9.9, which means when the internal control system of payroll and payroll accounting information system increased until an optimal (10), then the payroll to 9.9, then the hypothesis is Ha accepted conducted with simultaneous test done of F count 72> F table 3.47 which means there is influence between the internal control system of payroll and payroll accounting information system to the payroll at PT. PLN (Persero) Distribution of Jakarta and Tangerang Area Bulungan.